Penerapan Model JIGSAW Memanfaatkan Teknologi Smart TV untuk Meningkatkan Kemampuan Menulis Teks Ulasan Kelas VIII di SMPIT Al-Irsyad Al-Islamiyyah Karawang - Khaerunnisa, Dona Putri; Muhtarom, Imam; Sugiarti, Dewi Herlina (Universitas Tidar, 2024)
Indonesian language learning in schools requires the right learning model to maximize student learning outcomes. This study aims to determine the effect of applying the Jigsaw model utilizing smart TV technology in improving students' review text writing ability. This research is a quantitative research. The research method used was quasi-experiment with Nonequaivalent Control Group Design. The samples of this study were class VIII Gaza as the experimental class and class VIII Kuffah as the control class. The data collection technique in this study used a description test technique. The results showed that the application of the Jigsaw model utilizing smart TV technology had a significant effect on students' review text writing ability. This can be proven from the average value of the experimental class on the pretest 64.57 and posttest 87.39. While the average value of the control class on the pretest 38,91 and posttest 66,96. Based on the results of the N- Gain calculation, there is a significant effectiveness, namely the experimental class 65.01 which is quite effective and the control class 44.91 which is less effective. In knowing the significant difference, the difference test of two average N-Gain scores was conducted. The results obtained are the significance value (2-tailed) 0.005 <0.05, so it is stated that Ha is accepted, meaning that the ability to write student review texts with the application of the Jigsaw learning model is better than students who do the Jigsaw learning model.